Demographic Factors and Local Government Reform - Chernyshev, Konstantin Anatolyevich (Economy of Regions, 2015)
The subject of the article is to analyze the changes in the grid of municipalities in the Russian Federation during the reform of local government under the influence of demographic factors. The research based on a systems approach to the investigation of the regions where there is interaction between demographic and government subsystem. The main research method was to analyze the legislation and regional statistics. Detailed analysis of the demographic situation in the Kirov Oblast, the impact of natural and the migration decrease on change in the territorial organization of local self-government in the region are analyzed. The prospects of development of the municipal division under the influence of population are defined. It is concluded that in the present time, the grid municipalities in depopulated regions of Russia are not stable and will continue to vary according to the dynamics of population.